A canonical view on particle acceleration by electromagnetic pulses. (18th April 2022) - Russman, F.; Marini, S.; Rizzato, F.B.
Abstract : In the present work we investigate the dynamics of electrons under the action of wave packets of high-frequency electromagnetic carrier waves. When the group velocities of the packets are subluminal, electrons can be efficiently accelerated. We show that the whole process can be described by an accurate ponderomotive canonical formalism that includes relevant extensions of the original ponderomotive approach applied to carriers moving at the speed of light. Single-particle simulations validate our analytical approach and show that extended canonical methods provide better agreement with numerics than previous investigations. In particular, we obtain a precise relationship between the wave amplitude and group velocity for optimum acceleration of initially stationary targets.